Hungry girl to the max! : the ultimate guilt-free cookbook - Lillien, Lisa (New York : St. Martin's Griffin, 2012)
A collection of over six hundred low-calorie recipes includes ideas ranging from crockpot meals and comfort foods to single-serving recipes and dishes with five ingredients or fewer.
Includes index.
Keywords: Low-calorie diet -- Recipes; Low-calorie diet; Cookbooks; Cookbooks